2001
DOI: 10.1103/physreve.63.036132
|View full text |Cite
|
Sign up to set email alerts
|

Heat kernel regularization of the effective action for stochastic reaction-diffusion equations

Abstract: The presence of fluctuations and non-linear interactions can lead to scale dependence in the parameters appearing in stochastic differential equations. Stochastic dynamics can be formulated in terms of functional integrals. In this paper we apply the heat kernel method to study the short distance renormalizability of a stochastic (polynomial) reaction-diffusion equation with real additive noise. We calculate the one-loop effective action and its ultraviolet scale dependent divergences. We show that for white n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…As reported [9,16], in other approaches the effective potential is useful only for stationary or static regimes; the approach presented here can be used to study those cases, the complete temporal evolution of (1) and also the equilibria and stability states. The present potential formulation is based on a classical mechanics approach, there is no need of auxiliary or ghost fields.…”
Section: The Hojman Et Al Methods Enables Us To Writementioning
confidence: 99%
See 1 more Smart Citation
“…As reported [9,16], in other approaches the effective potential is useful only for stationary or static regimes; the approach presented here can be used to study those cases, the complete temporal evolution of (1) and also the equilibria and stability states. The present potential formulation is based on a classical mechanics approach, there is no need of auxiliary or ghost fields.…”
Section: The Hojman Et Al Methods Enables Us To Writementioning
confidence: 99%
“…In a more recent paper [16] Hochberg et al have reported that their effective potential does not provide information about the time evolution and spatial inhomogeneities of the system under consideration, and the effective action is very difficult to calculate exactly.…”
mentioning
confidence: 99%